If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -0.2x = 520 Solving X + -0.2x = 520 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '0.2x' to each side of the equation. X + -0.2x + 0.2x = 520 + 0.2x Combine like terms: -0.2x + 0.2x = 0.0 X + 0.0 = 520 + 0.2x X = 520 + 0.2x Simplifying X = 520 + 0.2x
| 6x+29=-25 | | f(x)=x-(3/lnx) | | f(x)=x-3/lnx | | 18x-5x+4=28 | | 8x-(6x+5)=4x-21 | | 4x+2=(x-5) | | 4y+2=3(y-5) | | 3(3+3x)=8(x-2) | | 3(3+3)=8(x-2) | | 6x/2-3 | | 7*7*7*7*7=212 | | 7*5=212 | | 3t-9=7-1 | | 6x+3y=15.75 | | 7z-5-5(z+1)=-(4z+7) | | 1/3*4x | | 2k^2+7k-30=0 | | 7-q/4=2.5 | | 7-4=2.5 | | -3x+10y=0 | | sx+ty=ufory | | 8v=-18 | | 4lnx+6=0 | | 7(x+2)-8(4+3x)=47 | | 7(x-2)-8(4+3x)=47 | | 9x^2-100x+1000=0 | | 4x-t=14 | | (9-3g)-(3+12g)= | | log(x-1)-log(x+1)-log(8)=-2 | | 2x-7y+z=-5 | | x^3+4x^2+60x-17=0 | | log(x-1)-2*log(x+1)-log(8)=-2 |